THE EFFECTS OF PSYCHOEDUCATIONAL METHODS ON COLLEGE STUDENTS’ ATTITUDES TOWARD PTSD - Amna, Zaujatul; Lin, Hsiu Chen (Jurnal Ilmiah Peuradeun, 2016)
This study investigated the effectiveness of psycho-education methods on college students’ attitudes toward post traumatic stress disorder. Analysis of results indicated that lecturing was the most effective psycho-educational method to obtain attitudinal changes. The effects of psycho-education methods of a short-duration intervention for college students' positive attitudes toward PTSD. Findings from the study led to the results that a short-duration of psycho-education intervention on PTSD effectively increases college students' attitudes toward post traumatic stress disorder, reduces negative attitudes towards PTSD.